Prolongamentos na fala de adultos com e sem gagueira - Silva, Pâmila Bento Da; Fabron, Eliana Maria Gradin; Picoloto, Luana Altran; Oliveira, Cristiane Moço Canhetti De (ABRAMO Associação Brasileira de Motricidade Orofacial, 2016)
ABSTRACTPurpose: to carry out a quantitative and qualitative analysis of the prolongations of adults who stutter and who not stutter.Methods: participants were divided into two groups: Research Group (RG, 15 adults who stutter) and Control Group (GC, 15 fluent adults). Procedures were: fluency assessment, Stuttering Severity Instrument and quantitative and qualitative analyzes of the prolongations.Results: there was a greater number of non hesitative prolongations in RG, whereas CG showed more hesitative prolongations in relation to the total of disfluencies. Non hesitative prolongations occurred more frequently in the initial and monosyllabic words, and in the medial position of the sentence in RG. Regarding the muscular tension and duration, a difference was observed for the muscular tension in the non hesitative prolongations, with higher mean value for RG.Conclusion: non hesitative prolongations occurred more frequently in RG, in initial words, monosyllables, and medial position of the sentence. Qualitatively, the muscular tension was a typical characteristic of non hesitative prolongations in RG. No differences were found for hesitative prolongations between the groups in relation to the frequency of the total of speech, the position of prolongations in the words and in the sentences, and for the qualitative characteristics, regarding to muscular tension and duration.

RESUMOObjetivo: realizar uma análise quantitativa e qualitativa dos prolongamentos de adultos com e sem gagueira.Métodos: os participantes foram divididos em: Grupo de Pesquisa (GP, 15 adultos com gagueira) e Grupo Controle (GC, 15 fluentes). Os procedimentos utilizados foram: avaliação da fluência, Instrumento de Gravidade da Gagueira e análises quantitativa e qualitativa dos prolongamentos.Resultados: GP mostrou maior número de prolongamentos não hesitativos, enquanto que GC mostrou maior ocorrência de prolongamentos hesitativos em relação ao total das disfluências. Prolongamentos não hesitativos ocorreram com maior frequência na palavra inicial e monossilábica, bem como na posição medial da frase para GP. Em relação à tensão muscular e duração, observou-se diferença apenas para a tensão muscular nos prolongamentos não hesitativos com maior média de ocorrência para GP.Conclusão: os prolongamentos não hesitativos ocorreram com maior frequência no GP, nas palavras iniciais, monossílabos e na posição medial da frase. Qualitativamente a tensão muscular foi uma característica típica dos prolongamentos não hesitativos no GP. Com relação aos prolongamentos hesitativos houve semelhança entre os adultos dos dois grupos quanto à frequência em relação ao total da fala, a posição dos prolongamentos nas palavras e nas frases e nos aspectos qualitativos, relacionados a tensão muscular e duração.
Prolongations in the speech of adults who do and do not stutter
Keywords: Speech Language and Hearing Sciences; Speech; Stuttering; Speech Disorders; Evaluation; Adult; Fonoaudiologia; Fala; Gagueira; Distúrbios da Fala; Avaliação; Adulto